Seismic Vulnerability of a Rockfill Dam through Different Displacement-based Approaches. Issue 1 (2nd January 2022) - Vecchietti, Alessia; Cecconi, Manuela; Russo, Giacomo; Pane, Vincenzo
ABSTRACT: The paper focuses on the assessment of the seismic performance of Menta Dam, a bituminous faced-rockfill dam located in Southern Italy. The dam was designed in the '70s and a comprehensive assessment of hydraulic and seismic vulnerability has been recently performed according to most recent Italian dam regulations. The present work aims at predicting the displacement capacity of the embankment as an indicator to assess the overall seismic vulnerability of the system. To this aim, different displacement-based methods, which can be classified in the framework of simplified dynamic analyses, have been applied. The results of empirical approaches and of Newmark's type dynamic analyses are compared to the ones obtained by a novel application of Direct Displacement-Based Assessment (DDBA) method for embankment structures. The latter approach seems to be promising, since it is capable to furnish the maximum displacement experienced by the dam crest for progressively increasing seismic actions, and its probability of exceedance; hence, the likelihood of reaching a threshold damaged condition can be deduced and usefully plotted in terms of fragility curves.